Membrane electrode for hydrogen fuel cell vehicle, preparation method and application

Through indirect transfer method and expanded polytetrafluoroethylene (ePTFE) film as transfer medium, a flexible catalyst coating structure is designed, which solves the problems of low utilization efficiency of precious metal catalysts for hydrogen fuel cell membrane electrodes and difficulty in batch production, and achieves high-performance and low-cost membrane electrode production.

CN119601727APending Publication Date: 2025-03-11LU HYDROGEN TIMES (SHANDONG) HYDROGEN POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411549145.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the precious metal catalyst utilization efficiency of hydrogen fuel cell membrane electrodes is low, and it is difficult to achieve mass production through direct coating.

Method used

By using indirect transfer method, a flexible catalyst coating structure is designed through an expanded polytetrafluoroethylene (ePTFE) film as a transfer medium, to improve the three-phase reaction interface and reduce the amount of precious metal catalyst.

Benefits of technology

It effectively solves the swelling problem, improves the catalyst utilization rate, reduces the amount of precious metals, and realizes the mass production of high-performance and low-cost hydrogen fuel cell automotive membrane electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114607870000081
    Figure BDA0005114607870000081
  • Figure BDA0005114607870000091
    Figure BDA0005114607870000091
  • Figure BDA0005114607870000092
    Figure BDA0005114607870000092
Patent Text Reader

Abstract

The invention belongs to the technical field of hydrogen fuel cells, and particularly relates to a membrane electrode for a hydrogen fuel cell vehicle, a preparation method and application. The fuel cell membrane electrode comprises an anode gas diffusion layer, a catalyst coating proton membrane (CCM), a cathode gas diffusion layer and a sealing frame, the CCM is prepared by taking an ePTFE (expanded polytetrafluoroethylene) membrane with a reticular porous structure as a transfer medium through an indirect transfer printing method. According to the invention, the flexible design of the catalyst coating structure of the catalyst coating proton membrane CCM can be realized, the three-phase reaction interface of the fuel cell can be increased, the efficient transfer of protons in the catalyst layer and the use efficiency of the catalyst can be improved, and the dosage of the noble metal catalyst can be obviously reduced; the problem of swelling of the perfluorosulfonic acid type proton exchange membrane caused by a direct coating method is effectively solved, and the method is suitable for batch production and preparation of fuel cell membrane electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen fuel cells, and in particular to a membrane electrode for hydrogen fuel cell vehicles, a preparation method and applications thereof. Background Art

[0002] A fuel cell is an energy conversion device that uses the principle of electrochemical reaction to directly convert the chemical energy in fuel and oxidant into electrical energy. Since it does not go through the Carnot cycle, it has the advantages of high energy density, fast start-up and zero emissions, and has broad application prospects in transportation, fixed power supply and backup power supply. When the fuel is hydrogen, it is also called a hydrogen fuel cell. The application advantages of hydrogen fuel cells in the logistics and transportation industry are more obvious, mainly reflected in reducing carbon emissions, quickly replenishing energy and efficient operation. Compared with traditional diesel vehicles, hydrogen fuel cell vehicles can reduce carbon emissions by 19.6 kilograms per 100 kilometers, and can reduce carbon emissions by 19.6 tons based on an annual driving of 100,000 kilometers. In addition, the energy replenishment speed of hydrogen fuel cell vehicles is faster than that of electric vehicles, which can better meet the logistics industry's demand for efficient operation. Therefore, fuel cell vehicles have become a research hotspot in countries around the world.

[0003] The membrane electrode is the core component of hydrogen fuel cells. It is the place where chemical energy is converted into electrical energy during the operation of the battery, and plays a key role in the performance of PEMFC. The performance of the membrane electrode assembly (MEA) is closely related to the structure in addition to the material. Therefore, improving the preparation materials and preparation methods of the membrane electrode, as well as optimizing its structure, is one of the important ways to improve the performance of MEA.

[0004] The membrane electrode is usually composed of a proton exchange membrane and electrodes arranged on both surfaces of the proton exchange membrane. Usually, the electrode includes a catalyst layer and a gas diffusion layer, and the catalyst layer is arranged between the gas diffusion layer and the proton exchange membrane. The electrochemical reaction carried out in the catalyst layer is carried out on a three-phase interface with reaction gas, protons and electrons at the same time. The catalyst nanoparticles in the catalyst layer play a catalytic role and conduct electrons, the polymer electrolyte resin plays a role in conducting protons, and the micropores in the electrode play a role in transferring reactants (hydrogen, oxygen) and products (water). At present, the best hydrogen fuel cell catalyst is still the precious metal platinum, so the amount of platinum catalyst used directly affects the battery performance and cost.

[0005] In the prior art, there are two methods for preparing the catalyst layer, one is a direct method, in which the catalyst slurry is directly coated on the proton exchange membrane, and the other is an indirect method, in which the catalyst slurry is first coated on a transfer medium, and then the catalyst layer is transferred to the proton exchange membrane by hot pressing. Although the direct method is simple to operate, the catalyst slurry generally contains alcohol solvents, and direct coating easily leads to the problem of swelling of the proton exchange membrane. Although process improvements such as electrostatic direct spraying and ultrasonic direct spraying have been adopted, batch preparation is still difficult, and the indirect method can better solve the problem of swelling and wrinkling of the proton exchange membrane. This method can effectively avoid swelling and deformation of the proton exchange membrane when it encounters a solvent, and the catalyst layer is in good contact with the membrane, but there are still problems such as low utilization of the catalyst, the need to improve the three-phase reaction interface, and large amount of precious metal catalysts.

[0006] In order to improve the utilization efficiency of precious metal catalysts and solve the problem of difficulty in mass production by direct coating, it is necessary to propose a new membrane electrode preparation method, which is conducive to the mass production of high-performance and low-cost membrane electrodes for hydrogen fuel cell vehicles. Summary of the invention

[0007] In view of the problems of low utilization efficiency of precious metals in the preparation of fuel cell membrane electrodes and difficulty in mass production by direct coating method in the prior art, the present invention proposes a method for preparing membrane electrodes for hydrogen fuel cell vehicles, which is simple to operate and not only solves the problem of swelling and wrinkling of perfluorosulfonic acid proton exchange membranes when they are directly coated with solvents, but also the catalyst coating structure design in the catalyst coating proton membrane CCM is flexible, thereby realizing the mass production of high-performance and low-cost membrane electrodes for fuel cell vehicles. In addition, the present invention also provides a fuel cell membrane electrode and a fuel cell prepared by the method.

[0008] In order to solve the above problems, the present invention adopts the following technical solutions:

[0009] A membrane electrode for a hydrogen fuel cell vehicle, wherein the total thickness of the membrane electrode for a hydrogen fuel cell vehicle is 350-550 μm; the structure of the membrane electrode for a hydrogen fuel cell vehicle comprises an anode gas diffusion layer, a catalyst coating proton membrane CCM, a cathode gas diffusion layer and a sealing frame; the CCM comprises an anode catalyst layer, a perfluorosulfonic acid type proton exchange membrane and a cathode catalyst layer, wherein the anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the perfluorosulfonic acid type proton exchange membrane;

[0010] An anode gas diffusion layer is provided on one side of the CCM close to the anode catalyst layer;

[0011] An anode gas diffusion layer is disposed on one side of the CCM close to the cathode catalyst layer;

[0012] The sealing frame is used to isolate the anode side from the cathode side to prevent fuel penetration.

[0013] Furthermore, the thickness of the anode gas diffusion layer is 180-250 μm, and the anode gas diffusion layer is one of carbon fiber paper or carbon fiber cloth; the thickness of the cathode gas diffusion layer is 180-250 μm, and the cathode gas diffusion layer is one of carbon fiber paper or carbon fiber cloth.

[0014] Furthermore, the thickness of the catalyst coating proton membrane CCM is 20-35 μm, and the precious metal content is 0.25-0.5 mg / cm 2 .

[0015] Furthermore, the sealing frame material used for the sealing frame has a thickness of 50-150 μm, and the sealing frame material is one of polyethylene terephthalate PET, polyethylene naphthalate PEN, polyimide PI or polyetherimide PEI.

[0016] A method for preparing a membrane electrode for a hydrogen fuel cell vehicle, the method comprising the following steps:

[0017] S1, uniformly dispersing a perfluorosulfonic acid resin solution and a noble metal catalyst to prepare an anode catalyst slurry, and then coating the anode catalyst slurry on an expanded polytetrafluoroethylene (ePTFE) membrane to obtain a substrate coated with an anode catalyst layer;

[0018] S2, uniformly dispersing the perfluorosulfonic acid resin solution and the noble metal catalyst to prepare a cathode catalyst slurry, and then coating the cathode catalyst slurry on an expanded polytetrafluoroethylene (ePTFE) membrane to obtain a substrate coated with a cathode catalyst layer;

[0019] S3, disposing the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping a perfluorosulfonic acid proton exchange membrane, and disposing the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, applying thermal pressure to the substrate from the outside of both sides by a roller press, thereby simultaneously thermally transferring the anode catalyst layer and the cathode catalyst layer on both sides of the perfluorosulfonic acid proton exchange membrane, and peeling off the transfer medium on both sides of the perfluorosulfonic acid proton exchange membrane after cooling, to obtain a catalyst coated proton membrane CCM;

[0020] S4, using a sealing frame material to seal the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0021] S5. Assembling and preparing MEA: configuring an anode gas diffusion layer on the side of the CCM with a sealed frame obtained in the above step S4 close to the anode catalyst layer, and configuring a cathode gas diffusion layer on the other side of the CCM close to the cathode catalyst layer, and assembling by hot pressing to obtain a membrane electrode MEA for hydrogen fuel cell vehicles.

[0022] Furthermore, in the anode catalyst slurry in step S1, the type of precious metal catalyst is one or a mixture of two or more of Pt / C catalyst, PtCo / C catalyst, IrO2, and PtIr / C catalyst, the concentration of the perfluorosulfonic acid resin solution is 5 to 20 wt%, and the mass ratio of the perfluorosulfonic acid resin solution to the precious metal catalyst is 1 to 8:1.

[0023] Furthermore, in the cathode catalyst slurry in step S2, the type of precious metal catalyst is one or a mixture of two or more of Pt / C, PtCo / C, PtNi / C and PtPd / C catalysts, the concentration of the perfluorosulfonic acid resin solution is 5 to 20wt%, and the mass ratio of the perfluorosulfonic acid resin solution to the precious metal catalyst is 1 to 7:1.

[0024] Furthermore, the expanded polytetrafluoroethylene (ePTFE) membrane is a thin film with a mesh porous structure formed by connecting fine fibers, which is made of polyvinyl fluoride resin by stretching and other processing methods. It is designed according to the requirements of the catalyst coated proton membrane CCM, and the porous pore size is 0.2-0.9μm; the thickness is 50-100μm; and the contact angle is 95-105°.

[0025] Furthermore, the coating method of step S1 and step S2 is one of slit coating or blade coating, and the coating speed is 5-50 mm / s; the roller press setting parameters in step S3 are that the pressure of the two rollers against each other is 1-2 MPa and the temperature is 110-140°C; in the MEA assembly preparation in step S4, the hot pressing pressure is 10-25 kg / cm 2 , the hot pressing temperature is 80-110℃.

[0026] An application of a membrane electrode for a hydrogen fuel cell vehicle is used for a hydrogen fuel cell for the vehicle.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The present invention uses an indirect transfer method to effectively solve the swelling problem that is easy to occur during direct coating and the difficulty of mass production of existing processes such as electrostatic spraying and ultrasonic spraying.

[0029] (2) The present invention uses an expanded polytetrafluoroethylene (ePTFE) membrane with a mesh porous structure formed by connecting fine fibers as a transfer medium, and the catalyst layer structure in the catalyst-coated proton membrane (CCM) is flexibly designed, which is beneficial to increasing the three-phase reaction interface of the fuel cell, improving the catalyst utilization rate, and reducing the amount of precious metal catalysts, which is beneficial to reducing the preparation cost of membrane electrodes for hydrogen fuel cell vehicles.

[0030] (3) The preparation method of the present invention is simple and efficient, suitable for mass production, and can meet the development and application of hydrogen fuel cell tractors, heavy trucks, cold chain logistics vehicles and other transportation fields. DETAILED DESCRIPTION

[0031] In order to further illustrate the present invention, a membrane electrode for a hydrogen fuel cell vehicle, a preparation method, and a fuel cell provided by the present invention are described in detail below in combination with embodiments. However, they should not be understood as limiting the scope of protection of the present invention. Unless otherwise specified, the chemical reagents and medicines involved in the present invention are all commercially available. Unless otherwise specified, the methods involved are all conventional methods.

[0032] Example 1

[0033] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5% and a Pt / C catalyst with a Pt content of 60% were uniformly dispersed in a mass ratio of 6:1 to prepare an anode catalyst slurry. Then, the slit coating was performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.2 μm) with a thickness of 50 μm and a contact angle of 105°. The coating speed was 5 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.15 mg / cm 2 ;

[0034] S2. A 5% mass concentration of perfluorosulfonic acid resin solution and a Pt / C catalyst with a Pt content of 60% were dispersed evenly in a mass ratio of 5:1 to form a cathode catalyst slurry, and then slit-coated on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.2 μm) with a thickness of 50 μm and a contact angle of 105° at a coating speed of 5 mm / s. After drying, a substrate coated with a cathode catalyst layer was obtained, with a noble metal loading of 0.35 mg / cm 2 ;

[0035] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 12 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a way of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 1.5 MPa, and the temperature is 120°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane CCM with a thickness of 35 μm;

[0036] S4, using polyethylene naphthalate (PEN) with a sealing frame material of 75 μm thickness to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0037] S5, assembling and preparing MEA: The CCM with a sealed frame obtained in step S4 above is provided with an anode gas diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on one side close to the anode catalyst layer, and a cathode gas diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on the other side close to the cathode catalyst layer. The pressure is 10 kg / cm 2 The membrane electrode (MEA) for hydrogen fuel cell vehicles is obtained by hot pressing and assembling at a temperature of 110°C.

[0038] Preparation of fuel cells: Assemble the membrane electrode, current collecting plate, end plate and sealing materials into a fuel cell.

[0039] Example 2

[0040] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5% and a Pt / C catalyst with a Pt content of 60% were dispersed evenly in a mass ratio of 6:1 to prepare an anode catalyst slurry. Then, the slit coating was performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 50 μm and a contact angle of 95°. The coating speed was 5 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.05 mg / cm 2 ;

[0041] S2. Disperse a 5% perfluorosulfonic acid resin solution and a Pt / C catalyst with a Pt content of 60% at a mass ratio of 5:1 to form a cathode catalyst slurry. Then, slit coating is performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 50 μm and a contact angle of 95°. The coating speed is 5 mm / s. After drying, a substrate coated with a cathode catalyst layer is obtained. The precious metal loading is 0.25 mg / cm 2 ;

[0042] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 12 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 1.5 MPa, and the temperature is 120°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane (CCM) with a thickness of 27 μm;

[0043] S4, using polyethylene naphthalate (PEN) with a sealing frame material of 75 μm thickness to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0044] S5, assembling and preparing MEA: configuring an anode gas diffusion layer (250 μm thick, made of carbon fiber cloth) on the side of the CCM with the sealing frame material obtained in step S4 close to the anode catalyst layer, and configuring a cathode gas diffusion layer (250 μm thick, made of carbon fiber cloth) on the other side of the CCM close to the cathode catalyst layer, and 2 The membrane electrode (MEA) for hydrogen fuel cell vehicles is obtained by hot pressing and assembling at a temperature of 90°C.

[0045] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0046] Example 3

[0047] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5% and a Pt / C catalyst with a Pt content of 60% were dispersed evenly in a mass ratio of 6:1 to prepare a catalyst slurry. Then, the slit coating was performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 100 μm and a contact angle of 105°. The coating speed was 5 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.05 mg / cm 2 ;

[0048] S2. A perfluorosulfonic acid resin solution with a mass concentration of 5% and a PtCo / C catalyst with a Pt content of 50% were dispersed evenly in a mass ratio of 3:1 to form a catalyst slurry. Then, the slit coating was performed on an expanded tetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 50 μm and a contact angle of 105°. The coating speed was 5 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.2 mg / cm 2 ;

[0049] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 8 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 1.5 MPa, and the temperature is 120°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane (CCM) with a thickness of 20 μm;

[0050] S4, using a sealing frame material polyetherimide PEI with a thickness of 75 μm to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0051] S5, assembling and preparing MEA: configuring an anode diffusion layer (180 μm thick, made of carbon fiber paper) on the side of the CCM with the sealing frame material obtained in step S4 close to the anode catalyst layer, and configuring a cathode diffusion layer (180 μm thick, made of carbon fiber paper) on the other side of the CCM close to the cathode catalyst layer, by 2 , and hot-pressed and assembled at a temperature of 80°C to obtain a membrane electrode (MEA) for hydrogen fuel cell vehicles.

[0052] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0053] Example 4

[0054] S1. A perfluorosulfonic acid resin solution with a mass concentration of 20%, a Pt / C catalyst with a Pt content of 60%, and an IrO2 catalyst were dispersed evenly in a mass ratio of 1.8:0.95:0.05 to prepare a catalyst slurry. Then, the slit coating was performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.9 μm) with a thickness of 60 μm and a contact angle of 105°. The coating speed was 50 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.05 mg / cm 2 ;

[0055] S2. A perfluorosulfonic acid resin solution with a mass concentration of 20% and a Pt / C catalyst with a Pt content of 60% were dispersed evenly in a mass ratio of 1.3:1 to form a catalyst slurry, and then slit-coated on an expanded tetrafluoroethylene (ePTFE) membrane (pore size 0.9 μm) with a thickness of 60 μm and a contact angle of 105° at a coating speed of 50 mm / s. After drying, a substrate coated with a cathode catalyst layer was obtained, with a noble metal loading of 0.25 mg / cm 2 ;

[0056] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 12 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 2MPa, and the temperature is 140°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane (CCM) with a thickness of 28 μm;

[0057] S4, using a sealing frame material polyetherimide PEI with a thickness of 150 μm to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0058] S5, assembling and preparing MEA: configuring an anode diffusion layer (250 μm thick, made of carbon fiber cloth) on the side of the CCM with the sealing frame material obtained in step S4 close to the anode catalyst layer, and configuring a cathode diffusion layer (250 μm thick, made of carbon fiber cloth) on the other side of the CCM close to the cathode catalyst layer, by pressing at a pressure of 25 kg / cm 2 , and hot-pressed and assembled at a temperature of 80°C to obtain a membrane electrode (MEA) for hydrogen fuel cell vehicles.

[0059] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0060] Example 5

[0061] S1. A perfluorosulfonic acid resin solution with a mass concentration of 20% and a Pt / C catalyst with a Pt content of 60% were uniformly dispersed in a mass ratio of 1.8:1 to prepare a catalyst slurry, and then the slurry was scraped and coated on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.7 μm) with a thickness of 50 μm and a contact angle of 101°. The coating speed was 25 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained, and the precious metal loading was 0.05 mg / cm 2 ;

[0062] S2. A perfluorosulfonic acid resin solution with a mass concentration of 20% and a PtCo / C catalyst with a Pt content of 50% were dispersed evenly in a mass ratio of 1.5:1 to form a catalyst slurry, and then slit-coated on an expanded tetrafluoroethylene (ePTFE) porous membrane (pore size 0.7 μm) with a thickness of 60 μm and a contact angle of 101° at a coating speed of 50 mm / s. After drying, a substrate coated with a cathode catalyst layer was obtained, with a noble metal loading of 0.3 mg / cm 2 ;

[0063] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 8 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 1 MPa, and the temperature is 130°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane (CCM) with a thickness of 24 μm;

[0064] S4, using a sealing frame material polyetherimide PEI with a thickness of 75 μm to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0065] S5, assembling and preparing MEA: configuring an anode diffusion layer (180 μm thick, made of carbon fiber paper) on the side of the CCM with the sealing frame material obtained in step S4 close to the anode catalyst layer, and configuring a cathode diffusion layer (180 μm thick, made of carbon fiber paper) on the other side of the CCM close to the cathode catalyst layer, by 2 , hot pressing assembly at a temperature of 80°C to obtain a membrane electrode (MEA) for hydrogen fuel cell vehicles.

[0066] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0067] Example 6

[0068] S1. A perfluorosulfonic acid resin solution with a mass concentration of 10%, a Pt / C catalyst with a Pt content of 60%, and an IrO2 catalyst were dispersed evenly in a mass ratio of 3.6:0.95:0.05 to prepare a catalyst slurry. Then, the slit coating was performed on an expanded polytetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 50 μm and a contact angle of 105°. The coating speed was 50 mm / s. After drying, a substrate coated with an anode catalyst layer was obtained. The precious metal loading was 0.05 mg / cm 2 ;

[0069] S2. A perfluorosulfonic acid resin solution with a mass concentration of 10% and a Pt / C catalyst with a Pt content of 60% were dispersed evenly in a mass ratio of 2.5:1 to form a catalyst slurry, and then slit-coated on an expanded tetrafluoroethylene (ePTFE) membrane (pore size 0.5 μm) with a thickness of 50 μm and a contact angle of 105° at a coating speed of 50 mm / s. After drying, a substrate coated with a cathode catalyst layer was obtained, with a noble metal loading of 0.2 mg / cm 2 ;

[0070] S3, select a perfluorosulfonic acid type proton exchange membrane with a thickness of 12 μm, and place the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping the proton exchange membrane, and place the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, and use a roller press to apply thermal pressure from the outside of the above substrate, so as to simultaneously thermally transfer the anode catalyst layer and the cathode catalyst layer on both sides of the solid proton exchange membrane, the thermal pressure is 2MPa, and the temperature is 130°C. After cooling to room temperature, peel off the transfer medium on both sides of the proton exchange membrane to obtain a catalyst coated proton membrane (CCM) with a thickness of 23 μm;

[0071] S4, using polyimide PI, a sealing frame material with a thickness of 50 μm, to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0072] S5, assembling and preparing MEA: configuring an anode diffusion layer (250 μm thick, made of carbon fiber cloth) on the side of the CCM with the sealing frame material obtained in step S4 close to the anode catalyst layer, and configuring a cathode diffusion layer (250 μm thick, made of carbon fiber cloth) on the other side of the CCM close to the cathode catalyst layer, by pressing at a pressure of 25 kg / cm 2 , and hot-pressed and assembled at a temperature of 105°C to obtain a membrane electrode (MEA) for hydrogen fuel cell vehicles.

[0073] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0074] Comparative Example 1

[0075] The difference from Example 1 is the preparation method of the membrane electrode:

[0076] S1. A 5% perfluorosulfonic acid resin solution and a Pt / C catalyst with a Pt content of 60% are uniformly dispersed in a mass ratio of 6:1 to prepare a catalyst slurry. Then, the anode catalyst slurry is directly coated on one side of a perfluorosulfonic acid proton exchange membrane with a thickness of 12 μm by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer is obtained. The noble metal loading is 0.15 mg / cm 2 ;

[0077] S2, a 5% mass fraction of perfluorosulfonic acid resin solution and a Pt / C catalyst with a Pt content of 60% are uniformly dispersed in a mass ratio of 5:1 to form a cathode catalyst slurry, and then the cathode catalyst slurry is directly coated on the other side of the proton exchange membrane obtained in the above S1 by direct ultrasonic spraying. After drying, the coating of the cathode catalyst layer is completed, and finally a catalyst coated proton membrane (CCM) is obtained with a thickness of 37 μm and a total precious metal loading of 0.5 mg / cm 2 ;

[0078] S3, using polyethylene naphthalate (PEN) with a sealing frame material of 75 μm thickness to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0079] S4, assembling and preparing MEA: The CCM with the sealing frame material obtained in step S4 above is provided with an anode gas diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on the side close to the anode catalyst layer, and a cathode diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on the other side close to the cathode catalyst layer. 2 The membrane electrode (MEA) for hydrogen fuel cell vehicles is obtained by hot pressing and assembling at a temperature of 110°C.

[0080] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0081] Comparative Example 2

[0082] The difference from Example 6 is the preparation method of the membrane electrode:

[0083] S1. A 10% perfluorosulfonic acid resin solution, a Pt / C catalyst with a Pt content of 60%, and an IrO2 catalyst are uniformly dispersed in a mass ratio of 3.6:0.95:0.05 to prepare a catalyst slurry. Then, the anode catalyst slurry is directly coated on one side of a perfluorosulfonic acid proton exchange membrane with a thickness of 12 μm by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer is obtained. The precious metal loading is 0.05 mg / cm 2 ;

[0084] S2, a perfluorosulfonic acid resin solution with a mass fraction of 10% and a Pt / C catalyst with a Pt content of 60% are uniformly dispersed in a mass ratio of 2.5:1 to form a cathode catalyst slurry, and then the cathode catalyst slurry is directly coated on the other side of the proton exchange membrane obtained in the above S1 by direct ultrasonic spraying. After drying, the coating of the cathode catalyst layer is completed, and finally a catalyst coated proton membrane (CCM) is obtained with a thickness of 24 μm and a total precious metal loading of 0.25 mg / cm 2 ;

[0085] S3, using polyimide PI, a sealing frame material with a thickness of 50 μm, to seal and package the CCM obtained in the above step S3 to obtain a CCM with a sealing frame;

[0086] S4, assembling and preparing MEA: The CCM with the sealing frame material obtained in step S4 above is provided with an anode gas diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on the side close to the anode catalyst layer, and a cathode diffusion layer (with a thickness of 250 μm and made of carbon fiber cloth) on the other side close to the cathode catalyst layer. 2 The membrane electrode (MEA) for hydrogen fuel cell vehicles is obtained by hot pressing and assembling at a temperature of 105°C.

[0087] Preparation of fuel cells: Assemble membrane electrode, current collecting plate and sealing materials into fuel cells.

[0088] The fuel cells prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were subjected to the following tests:

[0089] (1) Platinum loading test: The platinum loading of the anode catalyst layer and the cathode catalyst layer in the membrane electrode was tested using a handheld XRF spectrometer. One point was taken every 5 cm in the length direction (4 points in total) and one point was taken every 5 cm in the width direction (4 points in total), and the average value was calculated. The results are shown in Table 1.

[0090] (2) Fuel cell test: The test conditions were H2 / air stoichiometric ratio: 1.5 / 2.5: air back pressure 0.1 MPa, anode cathode humidification 80%, fuel cell operating temperature 78°C. The test results are shown in Table 1.

[0091] Table 1 Platinum loading test results

[0092]

[0093]

[0094] Table 2 Fuel cell performance results

[0095]

[0096] It can be seen from Table 1 and Table 2 that, compared with Comparative Examples 1 to 2, the membrane electrodes obtained in Examples 1 to 6 still exhibit good fuel cell performance when the precious metal platinum loading is reduced. The reason is that the membrane electrodes prepared in Examples 1 to 6 are obtained by an indirect method of forming an expanded polytetrafluoroethylene (ePTFE) membrane on a transfer medium to obtain a catalyst layer, which can not only effectively prevent the proton exchange membrane from swelling and deforming when encountering a solvent, but also provide good contact between the catalyst layer and the membrane, thereby improving the utilization rate of the precious metal catalyst, and increasing the three-phase reaction interface of the fuel cell. Therefore, even if the amount of the precious metal catalyst is reduced, good fuel cell performance can still be exhibited.

Claims

1. A membrane electrode for a hydrogen fuel cell vehicle, characterized in that: The total thickness of the membrane electrode for hydrogen fuel cell vehicle is 350-550 μm; the structure of the membrane electrode for hydrogen fuel cell vehicle includes an anode gas diffusion layer, a catalyst coating proton membrane CCM, a cathode gas diffusion layer and a sealing frame; the CCM includes an anode catalyst layer, a perfluorosulfonic acid proton exchange membrane and a cathode catalyst layer, wherein the anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the perfluorosulfonic acid proton exchange membrane; An anode gas diffusion layer is provided on one side of the CCM close to the anode catalyst layer; An anode gas diffusion layer is disposed on one side of the CCM close to the cathode catalyst layer; The sealing frame is used to isolate the anode side from the cathode side to prevent fuel penetration.

2. A membrane electrode for a hydrogen fuel cell vehicle according to claim 1, characterized in that: The thickness of the anode gas diffusion layer is 180-250 μm, and the anode gas diffusion layer is one of carbon fiber paper or carbon fiber cloth; the thickness of the cathode gas diffusion layer is 180-250 μm, and the cathode gas diffusion layer is one of carbon fiber paper or carbon fiber cloth.

3. The membrane electrode for hydrogen fuel cell vehicle according to claim 1, characterized in that: The thickness of the catalyst coating proton membrane CCM is 20-35 μm, and the precious metal content is 0.25-0.5 mg / cm 2 .

4. The membrane electrode for hydrogen fuel cell vehicle according to claim 1, characterized in that: The sealing frame material used in the sealing frame has a thickness of 50-150 μm, and the sealing frame material is one of polyethylene terephthalate PET, polyethylene naphthalate PEN, polyimide PI or polyetherimide PEI.

5. The method for preparing a membrane electrode for a hydrogen fuel cell vehicle according to any one of claims 1 to 4, characterized in that: The method for preparing the membrane electrode for hydrogen fuel cell vehicle comprises the following steps: S1, uniformly dispersing a perfluorosulfonic acid resin solution and a noble metal catalyst to prepare an anode catalyst slurry, and then coating the anode catalyst slurry on an expanded polytetrafluoroethylene membrane to obtain a substrate coated with an anode catalyst layer; S2, uniformly dispersing the perfluorosulfonic acid resin solution and the noble metal catalyst to prepare a cathode catalyst slurry, and then coating the cathode catalyst slurry on an expanded polytetrafluoroethylene membrane to obtain a substrate coated with a cathode catalyst layer; S3, disposing the substrate coated with the anode catalyst layer obtained in the above step S1 on one side in a manner of clamping a perfluorosulfonic acid proton exchange membrane, and disposing the substrate coated with the cathode catalyst layer obtained in the above step S2 on the other side, applying thermal pressure to the substrate from the outside of both sides by a roller press, thereby simultaneously thermally transferring the anode catalyst layer and the cathode catalyst layer on both sides of the perfluorosulfonic acid proton exchange membrane, and peeling off the transfer medium on both sides of the perfluorosulfonic acid proton exchange membrane after cooling, to obtain a catalyst coated proton membrane CCM; S4, using a sealing frame material to seal the CCM obtained in the above step S3 to obtain a CCM with a sealing frame; S5. Assembling and preparing MEA: configuring an anode gas diffusion layer on the side of the CCM with a sealed frame obtained in the above step S4 close to the anode catalyst layer, and configuring a cathode gas diffusion layer on the other side of the CCM close to the cathode catalyst layer, and assembling by hot pressing to obtain a membrane electrode MEA for hydrogen fuel cell vehicles.

6. The method for preparing a membrane electrode for a hydrogen fuel cell vehicle according to claim 5, characterized in that: In the anode catalyst slurry in step S1, the type of precious metal catalyst is one or a mixture of two or more of Pt / C catalyst, PtCo / C catalyst, IrO2, and PtIr / C catalyst, the concentration of perfluorosulfonic acid resin solution is 5-20wt%, and the mass ratio of perfluorosulfonic acid resin solution to precious metal catalyst is 1-8:

1.

7. The method for preparing a membrane electrode for a hydrogen fuel cell vehicle according to claim 5, characterized in that: In the cathode catalyst slurry in step S2, the type of precious metal catalyst is one or a mixture of two or more of Pt / C, PtCo / C, PtNi / C and PtPd / C catalysts, the concentration of the perfluorosulfonic acid resin solution is 5-20wt%, and the mass ratio of the perfluorosulfonic acid resin solution to the precious metal catalyst is 1-7:

1.

8. The method for preparing a membrane electrode for a hydrogen fuel cell vehicle according to claim 5, characterized in that: The expanded polytetrafluoroethylene membrane is a thin film with a reticular porous structure, which is designed according to the requirements of the catalyst coating proton membrane CCM, and has a porous pore size of 0.2-0.9 μm, a thickness of 50-100 μm, and a contact angle of 95-105°.

9. The method for preparing a membrane electrode for a hydrogen fuel cell vehicle according to claim 5, characterized in that: The coating method of step S1 and step S2 is one of slit coating or blade coating, and the coating speed is 5-50 mm / s; the roller press setting parameters in step S3 are that the pressure of the two rollers against each other is 1-2 MPa and the temperature is 110-140°C; in the MEA assembly preparation in step S4, the hot pressing pressure is 10-25 kg / cm 2 , the hot pressing temperature is 80-110℃.

10. Use of a membrane electrode for a hydrogen fuel cell vehicle as claimed in any one of claims 1 to 4, or a membrane electrode for a hydrogen fuel cell vehicle prepared by the preparation method as claimed in any one of claims 5 to 9, characterized in that: Hydrogen fuel cells for vehicles.